Strategi Pengembangan Sumberdaya Aparatur Pemerintah Di era Otonomi Daerah - Harmin, Udin (Jurnal Pelangi Ilmu, 2009)
The acts No ..32 year 2004 concerning government of area as completion uu no.22 in 1999. Because this uu have given meaning is new to nature and scope autonomous of area that is in the form of autonomy of area and fully. To support efficacy of execution of area autonomy of area and fully hence required various abilities from of the executors which inter alias cover: supporting facilities for adequate infrastructure, top-drawer and enough source of fund the which aparatur ready of relying and professional and also with system procedural officer. Human resources are the central factor in an organization, whatever its forms and goals, organization are formed based on various vision for human interest, so human is strategic factor in an institution or organization activity, either governmental or private organization in achieving their goals. The human resources development strategy also aimed as anticipative step in facing various problems and threats from the change dynamics and globalization currents in internal and external of organization. The formal education, education and training and employee empowerment variables simultaneously influence significantly toward the employee performance, but partially influence significantly, The next showed that fonnal education influence dominantly toward employee performance because through formal education able to develop three basic competences that is cognitive (intellectual), affective (moral/attitude), and psychomotor (skills) that support employees task as the society servant.